2016
DOI: 10.3390/ijms17060798
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Biological Effect of TiO2 and Hydroxyapatite Nanoparticles Used in Bone Repair and Replacement

Abstract: The adverse biological effect of nanoparticles is an unavoidable scientific problem because of their small size and high surface activity. In this review, we focus on nano-hydroxyapatite and TiO2 nanoparticles (NPs) to clarify the potential systemic toxicological effect and cytotoxic response of wear nanoparticles because they are attractive materials for bone implants and are widely investigated to promote the repair and reconstruction of bone. The wear nanoparticles would be prone to binding with proteins to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 103 publications
0
20
0
1
Order By: Relevance
“…Wear particles have the ability to induce the secretion of different cytokines, such as IL-6, IL-1β, or TNF-α in monocytes/macrophages, lymphocytes, osteoblasts, as well as fibroblasts [ 29 ]. In previous studies, we analyzed the biological effects of wear particles and corrosion products in all the mentioned cell types except for fibroblasts [ 19 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wear particles have the ability to induce the secretion of different cytokines, such as IL-6, IL-1β, or TNF-α in monocytes/macrophages, lymphocytes, osteoblasts, as well as fibroblasts [ 29 ]. In previous studies, we analyzed the biological effects of wear particles and corrosion products in all the mentioned cell types except for fibroblasts [ 19 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three 10 W of Sankyo Denki blacklight lamps with a center wavelength at 352 nm in parallel were used as the UV light sources. The samples were placed at the bottom of the glass cells (50 × 40 × 50 mm 3 internal dimensions) filled with the MB solution of concentrations of 10 −5 mol L −1 with the height of 10 mm. The measured irradiation intensity at the film surface was 0.59 mW cm −2 , which is relatively low compared with others [44,45] in order to prevent the MB diffusion in the solution from becoming a limitation factor for the photocatalysis experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Titanium dioxide, TiO 2 , is an inexpensive, non-toxic and chemically stable material. Its high refractive index and transparency for visible light have made it a widely used painting material, and its biological properties have made it a promising material for biomedical applications [1][2][3]. Recently, its strong oxidizing power under ultraviolet (UV) irradiation attracts great attention due to the applications of antibacterial, deodorizing, and remediation of environmental pollutions [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…While alower level of alkaline phosphatase (ALP) was found in NP-injected monkeys during 7-90 days p.i.,A LP is aless specific indicator of liver function [18b] and elevated ALP level is often observed after injection of NPs. [21] Parameters of complete blood count remained in anormal range,suggesting that GS-AuNPs did not induce systemic inflammation (Figure S17). Results of blood clotting tests confirmed that GS-AuNPs did not affect the coagulation system ( Figure S18).…”
Section: Angewandte Chemiementioning
confidence: 97%